2022
DOI: 10.1177/0271678x221101643
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity and developmental dynamics of LYVE-1 perivascular macrophages distribution in the mouse brain

Abstract: Brain perivascular macrophages (PVMs) are border-associated macrophages situated along blood vessels in the Virchow-Robin space and are thus found at a unique anatomical position between the endothelium and the parenchyma. Owing to their location and phagocytic capabilities, PVMs are regarded as important components that regulate various aspects of brain physiology in health and pathophysiological states. Here, we used LYVE-1 to identify PVMs in the mouse brain using brain-tissue sections and cleared whole-bra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 63 publications
3
18
0
Order By: Relevance
“…The Lyve1 + pvMs were located within the perivascular space around arterioles mainly, but not veins. This confirms a recent study in which Lyve1 + pvMs were detected around Cx40 positive arteries and large EphB4 positive veins 25 .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The Lyve1 + pvMs were located within the perivascular space around arterioles mainly, but not veins. This confirms a recent study in which Lyve1 + pvMs were detected around Cx40 positive arteries and large EphB4 positive veins 25 .…”
Section: Discussionsupporting
confidence: 92%
“…Recent studies have characterized pvMs and BAM within and outside the CNS, including the peripheral nervous system 23 , 27 , 28 . Particularly, parenchymal Lyve1 + pvMs were shown to be heterogenous by immunofluorescence on sections 25 .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…1 ). However, we cannot exclude the possibility that a small percentage of CD11b + cells represents vascular associated macrophages [ 46 ] known to have a role in regulation of vascular amyloid-beta plaques deposition [ 47 ]. Importantly, TNFα + cells co-expressing the CD11b (OX-42) marker represented the vast majority, ranging from 68 to 78%, at all hippocampal layers, in control mice, and at both time points studied.…”
Section: Resultsmentioning
confidence: 99%
“…We first validated two well-known markers for CNS borderassociated macrophages (BAMs): CD206 and lymphatic vessel endothelial hyaluronan receptor 1 (Lyve1; Jordão et al, 2019;Karam et al, 2022;Masuda et al, 2022). Double labeling with either CD206 or Lyve1 and ionized calcium-binding adaptor molecule 1 (Iba1) showed that both markers were present in Iba1-positive macrophage-like phenotype with amoeboid morphology, but they exhibited different degrees of coexistence with Iba1.…”
Section: Cd206 As a Biomarker Of Leptomeningeal Macrophagesmentioning
confidence: 99%